Investment projects: evaluation tools and methods - Moutinho, Nuno (2013)
Given the need to study di erent areas of analysis during the investment decision process, it is imperative to know which tools and methods are used by companies to assess various nancial and non- nancial aspects. As regards tools, we find that firms use checklists of analysis for non- fi nancial aspects, whereas they use their past experience in risk assessment, gathered from other projects. Records of past evaluation tend to be maintained in companies and those that use external advisors to evaluate projects tend to perform political analysis. As for the methods, companies use the identi cation of risk factors and assessment of ef fects and risk probabilities, the discussion and assessment of favorable and unfavorable factors to the project's execution, a coordinated analysis of fi nancial and non- financial aspects, and the creation of lists of risk indices, attributing a qualitative weight to each item. We have also analyzed the relationship between these tools and methods and each area of analysis in project evaluation.